2011
DOI: 10.1007/s10750-011-0960-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing biomonitoring protocols for shallow Arctic lakes using diatoms and artificial substrate samplers

Abstract: Growing concerns over effects of climate warming and other stressors on shallow Arctic lakes and ponds stimulate the need to develop and implement effective protocols to track changes in ecological integrity. This study assesses seasonal and spatial variability of periphytic diatom communities in a shallow Arctic lake in northern Yukon Territory to establish biomonitoring protocols. Artificial substrate samplers, which mimic macrophytes, allow direct measurement of biotic responses to shifting environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…It has been suggested that vegetation substrates may release carbohydrates and nutrients into the water to be taken up by epiphytic diatoms [ 88 , 89 ], potentially promoting growth and may partially explain the coincident timing of inferred production and epiphytes. The variability of the vegetative substrate, the additional competitive advantage it affords, and the lengthened growing season, which allows for greater complexity [ 90 ], may contribute to the increased diversity in epiphytic diatom communities in contrast to their epilithic and epipelic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that vegetation substrates may release carbohydrates and nutrients into the water to be taken up by epiphytic diatoms [ 88 , 89 ], potentially promoting growth and may partially explain the coincident timing of inferred production and epiphytes. The variability of the vegetative substrate, the additional competitive advantage it affords, and the lengthened growing season, which allows for greater complexity [ 90 ], may contribute to the increased diversity in epiphytic diatom communities in contrast to their epilithic and epipelic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been written about their use as a tool in the assessment of aquatic environment quality (De Pauw et al, 1994;Czerniawska-Kusza, 2004;MacDonald et al, 2012;Loke et al, 2014) or biomass production of phyto and zoobenthos (Moura et al, 2007;Plá & Alveal, 2012). In relation to inland waters, research has mainly focused on their habitat-creation role and concerns entire groups of benthic fauna (De Pauw et al, 1986, De Pauw et al, 1994Czerniawska-Kusza, 2004;Poznańska et al, 2009;Czarnecka et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of the value and need for coordinated hydrological and ecological monitoring to systematically observe the status and trends of aquatic ecosystems, we are working towards integrating the hydrological monitoring program with an ecological monitoring program, protocols of which were described by MacDonald et al (2012b). Northern ecosystem monitoring remains challenging.…”
Section: Discussionmentioning
confidence: 99%